Pharmacokinetic and pharmacodynamic actions of clozapine-N-oxide, clozapine, and compound 21 in DREADD-based chemogenetics in mice - Jendryka, Martin; Palchaudhuri, Monika; Ursu, Daniel; van der Veen, Bastiaan; Liss, Birgit; Kätzel, Dennis; Nissen, Wiebke; Pekcec, Anton (Scientific reports, 2019)
Muscarinic Designer Receptors Exclusively Activated by Designer Drugs (DREADD) gated by clozapine-N-oxide (CNO) allow selective G-protein cascade activation in genetically specified cell-types in vivo . Here we compare the pharmacokinetics, off-target effects and efficacy of CNO, clozapine (CLZ) and compound 21 (Cmpd-21) at the inhibitory DREADD human Gi-coupled M4 muscarinic receptor (hM4Di). The half maximal effective concentration (EC 50 ) of CLZ was substantially lower (0.42 nM) than CNO (8.1 nM); Cmpd-21 was intermediate (2.95 nM). CNO was back-converted to CLZ in mice, and CLZ accumulated in brain tissue. However, CNO itself also entered the brain, and free cerebrospinal fluid (CSF) levels were within the range to activate hM4Di directly, while free (CSF) CLZ levels remained below the detection limit. Furthermore, directly injected CLZ was strongly converted to its pharmacologically active metabolite, norclozapine. Cmpd-21 showed a superior brain penetration and long-lasting presence. Although we identified a wide range of CNO and Cmpd-21 off-targets, there was hardly any nonspecific behavioural effects among the parameters assessed by the 5-choice-serial-reaction-time task. Our results suggest that CNO (3–5 mg/kg) and Cmpd-21 (0.4–1 mg/kg) are suitable DREADD agonists, effective at latest 15 min after intraperitoneal application, but both require between-subject controls for unspecific effects.